Investigation of the Interplay between Circulating Lipids and IGF-I and Relevance to Breast Cancer Risk: An Observational and Mendelian Randomization Study - Tan, Vanessa Y; Bull, Caroline J; Biernacka, Kalina M; Teumer, Alexander; Richardson, Tom G; Sanderson, Eleanor; Corbin, Laura J; Dudding, Tom; Qi, Qibin; Kaplan, Robert C; Rotter, Jerome I; Friedrich, Nele; et al. (Cancer epidemiology, biomarkers & prevention, 2021)
Circulating lipids and insulin-like growth factor 1 (IGF-I) have been reliably associated with breast cancer. Observational studies suggest an interplay between lipids and IGF-I, however, whether these relationships are causal and if pathways from these phenotypes to breast cancer overlap is unclear. Mendelian randomization (MR) was conducted to estimate the relationship between lipids or IGF-I and breast cancer risk using genetic summary statistics for lipids (low-density lipoprotein cholesterol, LDL-C; high-density lipoprotein cholesterol, HDL-C; triglycerides, TGs), IGF-I and breast cancer from GLGC/UKBB ( = 239,119), CHARGE/UKBB ( = 252,547), and Breast Cancer Association Consortium ( = 247,173), respectively. Cross-sectional observational and MR analyses were conducted to assess the bi-directional relationship between lipids and IGF-I in SHIP ( = 3,812) and UKBB ( = 422,389), and using genetic summary statistics from GLGC ( = 188,577) and CHARGE/UKBB ( = 469,872). In multivariable MR (MVMR) analyses, the OR for breast cancer per 1-SD increase in HDL-C and TG was 1.08 [95% confidence interval (CI), 1.04-1.13] and 0.94 (95% CI, 0.89-0.98), respectively. The OR for breast cancer per 1-SD increase in IGF-I was 1.09 (95% CI, 1.04-1.15). MR analyses suggested a bi-directional TG-IGF-I relationship (TG-IGF-I per 1-SD: -0.13; 95% CI, -0.23 to -0.04; and IGF-I-TG per 1-SD: -0.11; 95% CI, -0.18 to -0.05). There was little evidence for a causal relationship between HDL-C and LDL-C with IGF-I. In MVMR analyses, associations of TG or IGF-I with breast cancer were robust to adjustment for IGF-I or TG, respectively. Our findings suggest a causal role of HDL-C, TG, and IGF-I in breast cancer. Observational and MR analyses support an interplay between IGF-I and TG; however, MVMR estimates suggest that TG and IGF-I may act independently to influence breast cancer. Our findings should be considered in the development of prevention strategies for breast cancer, where interventions are known to modify circulating lipids and IGF-I.